The Effects of SSRIs on Male Fertility - Badr, Miranna; Ibrahim, Ramsey; James, Britnei; Viltakis, Vanessa; Zakaib, Myriam (Université d'Ottawa | University of Ottawa, 2017)
BACKGROUND: It is estimated that by 2020, depression will be the second leading cause of world disability with predictions that by 2030 it will be the largest contributor to disease burden. While treatments for depression can vary, selective serotonin reuptake inhibitors (SSRIs) are currently the most prescribed antidepressants. Despite an increase of studies documenting the effects of antidepressants, there exists a limited number of studies on male SSRI use and the resulting effects on their fertility. OBJECTIVE: A structured review of the literature was conducted to assess the evidence regarding the effects of SSRI antidepressants on male fertility. Recent epidemiological studies were identified from the databases PubMed, Scopus, and Ovid. METHODS: The search was limited to publications in English and included the keywords SSRI, antidepressants, sperm, fertility, and male. In total, nine studies were found to be relevant to the structured literature review. RESULTS: One study on male rats observed an association of SSRI use and decreased fertility. Five studies concluded that there may be an association between the use of selective serotonin reuptake inhibitors and decreased sperm quality in both humans and rats. In studies where the discontinued use of SSRIs was evaluated, improvements in sperm concentration and motility were observed. Certain studies showed that changes in DNA fragmentation were observed in men taking paroxetine, allowing the potential for the change in DNA integrity to negatively impact male fertility. CONCLUSION: At this time, the literature shows evidence of the effect of certain SSRI antidepressants on male fertility in both rats and humans. Further study, including long term and large scale research, is needed to advance the validation of this conclusion.